Surviving the Assault? The Australian Disability Movement and the Neoliberal Workfare State - Soldatic, Karen; Chapman, A. (Routledge, 2010)
This article provides an analysis of the key areas of struggle for the Australian disability movement during the Howard years of government. After providing a brief overview of the Australian disability movement and its historical development, we then move to situate the struggles of the Australian disability movement within the broader context of welfare to work, one of the central tenets of neoliberal social policy restructuring. From here, three sites of struggle emerge that have been central to the Australian disability movement's struggles for representation, recognition and redistribution and principally include state restructuring of disability open labour market supports, state legitimation of disability sheltered workshops and, finally, the pensioner-categorization of disability within social security law and policy.